Nonstationary temperature fields and thermal stresses in a multilayer aircraft glazing - Smetankina, Natalia; Misiura, Serhii; Misiura, Ievgeniia (ISPEC, 2023)
A method for calculation of nonstationary thermal fields in a multilayer glazing of vehicles under the effect of impulse film heat sources is offered. The multilayer glazing is considered as a multilayer plate with complex shape made up of isotropic layers with constant thickness. The temperature on the side surface of the plate is zero. Convective heat transfer occurs on outer surfaces of the plate; on layers' interfaces film heat sources are arranged.
Keywords: laminated structures; deformation of structures; temperature field; multilayer glazing